Pengaruh Brand Image dan Efektivitas Iklan Terhadap Keputusan Pembelian Saus Sambal ABC Di Surabaya - Ryandini, Fadilla; Wardani, Nuruni Ika Kusuma (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The market in the food and beverage sector grow every year, providing sufficient opportunities for new companies wishing to enter the industry. The large variety of brands on the market provides consumers with many alternative choices when making purchases. This research aims to determine the influence of brand image and advertising effectiveness on purchasing decisions for ABC Sambal Sauce. This research is quantitative research with data collection methods using questionnaires. This study had a total of 100 respondents. The sampling technique used was nonprobability sampling with a purposive sampling method. Data was obtained by distributing questionnaires. The data analysis method uses Partial Least Square (PLS) analysis with the help of the Smart PLS 4.0 program. The research results show that Brand Image and Advertising Effectiveness have a positive and significant effect on Purchase Decisions for ABC Sambal Sauce in Surabaya. This is in line with the hypothesis so it can be said to be significant (positive).